SKALA KESANTUNAN TINDAK TUTUR EKSPRESIF-MENGELUH DALAM ANIME RELIFE - Elno Yulia; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the politeness scale of expressive speech acts of complaining found in the anime Relife episodes 1-13. The purpose of this study was to determine the politeness scale in expressive speech complaining. The object of research is the characters in the anime Relife episodes 1-13. This research is a descriptive qualitative research by interpreting the object under study based on Leech's (1983) politeness theory. The data was obtained by listening to the expressive utterances used by the characters and taking notes and then grouping them into each type. The results of this study indicate that the characters in the anime Relife episodes 1-13 use five types of Leech's politeness scale. Loss and gain scale, preference scale, indirectness scale, authority scale and social distance scale. In analyzing the use of the politeness scale in the ReLife anime , 21 data were found.Key Words: Politeness Scale, Expressive Speech Acts.